2014
DOI: 10.1038/ncomms5919
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of co- and post-translationally N-myristoylated proteomes in human cells

Abstract: Protein N-myristoylation is a ubiquitous co- and post-translational modification that has been implicated in the development and progression of a range of human diseases. Here, we report the global N-myristoylated proteome in human cells determined using quantitative chemical proteomics combined with potent and specific human N-myristoyltransferase (NMT) inhibition. Global quantification of N-myristoylation during normal growth or apoptosis allowed the identification of >100 N-myristoylated proteins, >95% of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
343
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 216 publications
(363 citation statements)
references
References 67 publications
20
343
0
Order By: Relevance
“…FRS2α contains the MGXXXS/T consensus sequence at the N-terminus for N-myristoylation modification (10). N-myristoyltransferase (NMT) catalyzes the myristoylation modification process by transferring the myristoyl group from myristoylCoA to the glycine at the N-terminus of a protein (15). In this study, we investigated a therapeutic approach to inhibit FGF/FGFRs-mediated oncogenic signaling and proliferation of cancer cells by blocking myristoylation of FRS2α.…”
Section: Inhibiting Myristoylation Of Frs2α In Fgfr-mediated Tumorsmentioning
confidence: 99%
“…FRS2α contains the MGXXXS/T consensus sequence at the N-terminus for N-myristoylation modification (10). N-myristoyltransferase (NMT) catalyzes the myristoylation modification process by transferring the myristoyl group from myristoylCoA to the glycine at the N-terminus of a protein (15). In this study, we investigated a therapeutic approach to inhibit FGF/FGFRs-mediated oncogenic signaling and proliferation of cancer cells by blocking myristoylation of FRS2α.…”
Section: Inhibiting Myristoylation Of Frs2α In Fgfr-mediated Tumorsmentioning
confidence: 99%
“…Computational prediction suggested that about 0.5% of all proteins in the human genome could be myristoylated (Maurer-Stroh et al, 2004). Indeed, the N-myristoylated proteome was recently studied in human cells, leading to the identification of more than 100 N-myristoylated proteins (Thinon et al, 2014). The myristoylated proteins include key components in intracellular signaling pathways, oncogenes, structural viral proteins but also common constitutive eukaryotic proteins.…”
Section: Myristic Acid and Protein N-terminal Myristoylationmentioning
confidence: 99%
“…Functionalized lipidation probes have been used to prove the exploitation of host-cell-mediated prenylation for membrane targeting of Legionella effectors (Ivanov et al 2010). Probes for a number of additional lipid modifications have been published and used to study a variety of diseases such as malaria and cancer (Thinon et al 2014;Wright et al 2014;Tate et al 2015). These could be useful to determine if T4SS effectors exploit other lipid modifications as membrane anchors.…”
Section: Functionalized Substrate Analogues To Profile Ptmsmentioning
confidence: 99%